Constraints Faced by Farmers in Adapting to Climate Change in North Bihar - Raj Lakshmi; V. K Singh; D. K Singh; Vavilala Priyanka; Monu Kumar (Indian Journal of Extension Education, 2025)
The study was conducted in 2025 in North Bihar to investigate the challenges faced by farmers in adapting to climate change. Districts Darbhanga and Sitamarhi were purposively chosen on the basis of high vulnerability to climate change.  To analyze the constraints faced by farmers, 192 respondents were selected randomly from selected villages. Farmers were surveyed through personal interviews, and data were analyzed using Garrett’s ranking technique to prioritize the constraints hindering adaptation to climate change. The constraints were divided into four categories, i.e., socio-personal constraints, institutional constraints, technical constraints, and financial constraints. The analysis revealed that socio-personal constraints, such as small size fragmented landholdings, and increasing labour scarcity, whereas institutional constraints such as lack of accurate and timely information about weather forecast and poor extension service on climate risk management were major constraints faced by farmers in adapting to climate change in north Bihar. Furthermore, the highly dependent nature of farmers on the monsoon and the lack of training on climate-smart agriculture practices were ranked as major technical constraints, whereas the high cost of inputs and the non-availability of timely inputs were financial constraints faced by farmers.